All‐trans retinoic acid reverses epithelial‐mesenchymal transition in paclitaxel‐resistant cells by inhibiting nuclear factor kappa B and upregulating gap junctions. Issue 1 (27th November 2018) - Shi, Guiling; Zheng, Xiaoli; Wu, Xiaojing; Wang, Siqi; Wang, Yijia; Xing, Fei
Abstract : Paclitaxel is a widely used chemotherapy drug, but development of resistance leads to treatment failure. Tumor cells that are treated with a sublethal dose of paclitaxel for a long period of time show the epithelial‐mesenchymal transition (EMT) phenotype, which leads to metastasis and resistance. All‐ trans retinoic acid (ATRA) is always used in combination with paclitaxel and can reverse EMT in many types of cancer cells. The ability of ATRA to reverse EMT in chemoresistant cells is still unknown. In the present study, the ability of ATRA to reverse EMT in paclitaxel‐resistant cells was investigated. Three colorectal cancer cell lines, HCT116, LoVo and CT26, were treated with sublethal doses of paclitaxel to create resistant cell lines. Western blotting, immunocytochemistry, and "parachute" dye‐coupling assays showed that ATRA reverses EMT, inhibits nuclear factor kappa B (NF‐κΒ), and upregulates gap junctions in paclitaxel‐resistant cells. Scratch wound‐healing and Transwell assays showed that ATRA decreases the migration and invasion abilities of paclitaxel‐resistant cells. In addition, the CT26 cell line was used in the Balb/c pulmonary metastasis model to show that ATRA reduces metastasis of paclitaxel‐resistant cells in vivo. Given these data, ATRA may reverse EMT by inhibiting NF‐κΒ and upregulating gap junctions in paclitaxel‐resistant cells. Abstract : In this study, the ability of ATRA to reverse EMT in paclitaxel‐resistant cells was investigated. In vivo and in vitro results showed that ATRA may reverse the EMT by inhibiting NF‐κΒ and upregulating gap junctions in paclitaxel‐resistant cells.